STRATEGI PENINGKATAN BRAND AWARENESS DAN AKTIFITAS PROMOSI DALAM SPORT EVENT (STUDI KASUS: EVENT MAYBANK BALI MARATHON 2019, GIANYAR, BALI) - Dwi Novita Cahyaningtyas Permatasari (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
Sporting events are one of the subjects in MICE related to the niche tourism development. Various promotional activities through sport event is used to increase brand awareness. It brings strong implications for many aspects of tourism development. Marathon has become very popular sport in 2019. Maybank made a breakthrough strategy to take advantage of this trend through organizing Maybank Bali Marathon 2019. Maybank Marathon achieved “Bronze Label” from World Athletics, became the first in Indonesia. However, Maybank's level of brand awareness in Bali needs to be evaluated. Based on the preliminary research conducted, most of the people were aware of the event but were not familiar with the bank's financial products. The method used in this study is a mix method by conducting survey of 100 respondents with random sampling technique and analyzed using descriptive analysis. Brand awareness is measured by characterizing four elements of David A. Aaker's theory namely top of mind, brand recall, brand recognition, unaware of brand. The results show that Maybank does not occupy the top of mind or brand recall levels, and there are only few respondents who recognize the logo and tagline, 60% of respondents do not aware Maybank brand. Interesting fact, although most respondents are not familiar with Maybank, almost all respondents (91%) are aware of the Maybank Bali Marathon event. Maybank's promotion scheme was analyzed using The Marketing Funnel theory by Adam Cohen and finally strategy was formulated using SWOT analysis.